(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
Associative teaching, grounded in the principles of associative learning, emphasizes linking new knowledge to pre-existing cognitive frameworks to facilitate comprehension and retention. This study investigates the effectiveness of associative teaching strategies in improving cognitive engagement and linguistic competence among secondary school students. Using a quasi-experimental design with control and experimental groups, the study assessed student performance through pre- and post-tests, observational data, and questionnaires. Results indicate that students exposed to associative teaching exhibited higher retention, deeper understanding, and improved language performance compared to the control group. Implications for curriculum design and pedagogical practices are discussed.